Relationships of circulating CD4+ T cell subsets and cytokines with the risk of relapse in patients with Crohn’s disease - Duclaux-Loras, Rémi; Boschetti, Gilles; Flourie, Bernard; Roblin, Xavier; Leluduec, Jean-Benoit; Paul, Stéphane; Almeras, Thibaut; Ruel, Karine; Buisson, Anthony; Bienvenu, Jacques; Josson, Cendrine; Jasnowski, Renaud; et al. (Frontiers in Immunology, 2022)
Background and aims We aimed to analyze circulating CD4+ T cell subsets and cytokines during the course of Crohn’s disease (CD). Methods and results CD4+ T cell subsets, ultrasensitive C-reactive protein (usCRP), and various serum cytokines (IL-6, IL-8, IL-10, IL-13, IL-17A, IL-23, TNFα, IFNγ, and TGFβ) were prospectively monitored every 3 months for 1 year, using multicolor flow cytometry and an ultrasensitive Erenna method in CD patients in remission at inclusion. Relapse occurred in 35 out of the 113 consecutive patients (31%). For patients in remission within 4 months prior to relapse and at the time of relapse, there was no significant difference in Th1, Th17, Treg, and double-positive CD4+ T cell subsets co-expressing either IFNγ and FOXP3, IL-17A and FOXP3, or IFNγ and IL-17A. On the contrary, in patients who remained in remission, the mean frequency and number of double-positive IL-17A+FOXP3+ CD4+ T cells and the level of usCRP were significantly higher (p ≤ 0.01) 1 to 4 months prior to relapse. At the time of relapse, only the IL-6 and usCRP levels were significantly higher (p ≤ 0.001) compared with those patients in remission. On multivariate analysis, a high number of double-positive IL-17A+FOXP3+ CD4+ T cells (≥1.4 cells/mm3) and elevated serum usCRP (≥3.44 mg/L) were two independent factors associated with risk of relapse. Conclusions Detection of circulating double-positive FOXP3+IL-17A+ CD4+ T cell subsets supports that T cell plasticity may reflect the inflammatory context of Crohn’s disease. Whether this subset contributes to the pathogenesis of CD relapse needs further studies.